Employee E-Performance Assessment Model with Personal Balanced Scorecard (Case Study of KH Bahaudin Mudhary University Madura) - R. Khaeru Ahmadi; Siti Sa’adah (Technium Social Sciences Journal, 2023)
Employee evaluation at the University of KH Bahaudin Mudhary Madura currently uses a separate method for giving assessments. Assessment of employees is carried out by superiors, subordinates and colleagues. Thus resulting in an assessment of existing employees to be not objective. Employee performance appraisal can later be used as a basis for establishing employee policies and leadership decision makers. This study raises a case that is evaluating employees based on the Personal Balanced Scorecard (PBSC) method. PBSC is a method that analyzes Key Performance Indicators (KPI) with a description of a person that includes four perspectives, namely Internal, External, Knowledge and Learning and Finance. Using the PBSC method in evaluating employee performance can help HR to assess employees objectively and without bias.